Dynamic mechanical properties of high nitrogen steel processed by wire and arc additive manufacturing - Meixia Qian; Shida Song; Yiming Guo; Kehong Wang (Journal of Materials Research and Technology)
A thin-walled sample of homemade high nitrogen steel wire (nitrogen content of 0.7 wt%) was prepared by wire and arc additive manufacturing, and its dynamic mechanical properties in the strain rate range of 1177 s−1 to 5063 s−1 were measured by split-Hopkinson pressure bar tests. The results showed that as-deposited high nitrogen steel had obvious strain rate strengthening effect, and its dynamic compressive properties in the deposition direction were better than that in the horizontal direction. Its dynamic compressive strength increased with the increase of strain rate (1303–1672 MPa), while the yield strength and strain hardening modulus increased first and then decreased. This is the result of the competition between the strain rate hardening and thermal softening effects caused by adiabatic temperature rise. Twinning was the main deformation mechanism of as-deposited high nitrogen steel under dynamic compression. The density of twins increased and the thickness decreased with the increase of strain rate. Twin intersections were observed in the twinning region and shears were found.